HUBUNGAN BEBAN KERJA PERAWAT DENGAN PELAKSANAAN RESTRAINT DI RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Niken " Widyastuti; Veny " Elita; Siti Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research is to determine the correlation  of nurse’s workload by  implementation of restraint in Tampan Psychiatric Hospital Riau Province. This research was using descriptive correlation design with cross sectional approach. The number of sample was 53 responden taken with using total sampling technique. The instrument of this research was questionnaire with 10 question of nurses workload and 20 statement of restraint procedures. Analysis were used in univariate analyzes to determine the frequency distribution and bivariate analyzes using chi square. The result of the research shows that respondent that had a light workload do the good implementation of restraint as many as 10 people (37,0%) and the respondent that had light workload do the bad implementation of restraint as many as 11 people (42,3%) while the respondent that had a hard workload do a good restraint as many as 17 people (63,0%) and respondent who had a hard workload do bad restraint as many as 15 people (57,7%.). The statistical result is p value (0,911) > α (0,05), it can be concluded there is no correlation of nurses workload with restraint implementation in tampan psychiatric hospital riau province. The result of the research can be used as evaluation to develop standard of nursing policy and SOP toward restraint implementation. Key words       : nurse, restraint implementation, Workload.